Dilemmas in fieldwork with migrants in an intermediate city (Polis (Santiago), 2024)
In this article I seek to reflect on some of the challenges involved in conducting ethnographic fieldwork with Senegalese migrants in Río Cuarto, an intermediate city in Córdoba, Argentina. This methodological path allowed me to establish a particular bond with my interlocutors, where assigned roles and relationships were strained according to different ideas and appreciations around issues such as migration and gender. The reflexivity on the practices developed in the field allowed me to recognise and reconsider errors, limits and difficulties in the enquiry, emerging dilemmas in the use of categories, positions and prejudices. This paper is the result of the development of qualitative collection and analysis techniques, such as the re-reading of field notes on informal conversations, research and systematisation of thematic background and observation in different places in the city and different degrees of participation.
Keywords: Migration; senegalese; ethnography; Río Cuarto